2018
DOI: 10.1159/000490721
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Thompson-Score for Long-Term Neurological and Cognitive Outcome in Term Newborns with Perinatal Asphyxia and Hypoxic-Ischemic Encephalopathy Undergoing Controlled Hypothermia Treatment

Abstract: Background: The so-called Thompson-score (TS) for newborns with hypoxic-ischemic encephalopathy (HIE) was developed before the introduction of controlled hypothermia as clinical routine. Information on the predictive value of TS in newborns undergoing therapeutic hypothermia to estimate long-term outcome is limited. Objectives: To determine the predictive value of TS to estimate long-term cognitive and neurological outcome in newborns with perinatal asphyxia treated with controlled hypothermia. Methods: Thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 7 publications
0
20
0
2
Order By: Relevance
“…Adverse long-term neurodevelopmental outcome is correlated with increasing severity of encephalopathy. [2][3][4][5] Therapeutic hypothermia (TH) has become standard of care for infants with moderate-to-severe HIE. 6 To be effective, TH must be commenced early, within 6 hours of birth.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse long-term neurodevelopmental outcome is correlated with increasing severity of encephalopathy. [2][3][4][5] Therapeutic hypothermia (TH) has become standard of care for infants with moderate-to-severe HIE. 6 To be effective, TH must be commenced early, within 6 hours of birth.…”
Section: Introductionmentioning
confidence: 99%
“…39 The Thompson score (►Table 1) has also been shown to be a good prognostic tool for predicting outcomes at 4 to 5 years old in HIE neonates treated with hypothermia. 40 Mendler et al showed that a maximal Thompson score 10 was associated with normal cognitive function. 40 Other groups demonstrated that the Thompson score is a good prognostic tool for predicting short-term outcomes.…”
Section: Clinical Neurological Examinationmentioning
confidence: 99%
“…40 Mendler et al showed that a maximal Thompson score 10 was associated with normal cognitive function. 40 Other groups demonstrated that the Thompson score is a good prognostic tool for predicting short-term outcomes. Higher Thompson scores have been associated with death before discharge, development of epilepsy, and severely abnormal amplitude-integrated electroencephalography (aEEG).…”
Section: Clinical Neurological Examinationmentioning
confidence: 99%
“…A score between 1 and 10 indicates mild HIE, a score between 11 and 15 is interpreted as moderate HIE and a score between 15 and 22 is considered as severe HIE 12,13 . Various studies have shown that the Thompson score can be used as a prognostic tool to predict the long-term neurodevelopmental and morbidity outcome in asphyxiated term newborns undergoing controlled hypothermia, with a higher score significantly associated with an adverse outcome 14 .…”
Section: The Hie Scorementioning
confidence: 99%